Determination of stabilized soil mixtures based on local biomass resources used to improve the quality of housing built by the population in the territory of Uige, Angola - Rufino, Jorge; Machado, Iván; Dias, Yosvany (Revista Ingeniería de Construcción, 2013)
The present investigation work, based on the socio-cultural, economic and climatic-environmental conditions of Uige Province, covers the available material, technique and human resources, as well constructive practices of traditional typologies of that region, in order to propose solutions for the great housing requirements in that territory. Due to diverse factors related to the characterization of this studied area, the housing stock built from earth or soil mixtures has a poor durability, thus increasing costs due to facilities´ deterioration and failures. Therefore, the present research proposes a way to increase soil stabilization, so as to improve the construction material characteristics. In that sense, this research work was focused in two aspects. On one hand, it was focused on the characterization of the studied area and the identification of problems, which impact the quality and durability of the already built housing stock. On the other hand, it was focused on the determination of the adapted stabilized-soil mixture made by means of recycled materials and the pozzolanic transformation of local agricultural residues.